Primavera di Praga, risveglio europeo - CACCAMO, FRANCESCO; Helan, Pavel; TRIA, MASSIMO (Biblioteca di Studi Slavistici, 2011)
The passage of time has not dulled the interest and fascination of the Prague Spring. Proof of this was provided on the occasion of the celebrations for the fortieth anniversary of the events in Czechoslovakia in 1968, greeted all over Europe including Italy by a packed programme of conferences, exhibitions and publications. This book too stemmed from an initiative organised to mark the anniversary, the conference entitled Primavera di Praga, risveglio europeo. Through the reflections of twelve Italian and Czech writers, it aims to help in the recollection and reconstruction of what was, despite its limitations and contradictions, at once the most considered and the most generous attempt at reform of real socialism.